Hire smart from the start : the entrepreneur's guide to finding, catching, and keeping the best talent for your company - Carvajal, Dave (AMACOM, 2018)
Don't rely on instincts alone. Hiring. Is. King. In Hire Smart from the Start, Dave Carvajal distills lessons gained from 20 years in the trenches, building out and staffing two enormously successful Internet startups and helping firms like Tumblr, Buddy Media, and Shutterstock land the talent they need to reach their greatest potential.